2018
DOI: 10.2147/ijn.s186888
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of zinc oxide nanoparticles using <em>Albizia lebbeck</em> stem bark, and evaluation of its antimicrobial, antioxidant, and cytotoxic activities on human breast cancer cell lines

Abstract: BackgroundBiocompatibility and stability of zinc oxide nanoparticles (ZnO NPs) synthesized using plants is an interesting research area of study in nanotechnology, due to its wide applications in biomedical, industrial, cell imaging, and biosensor fields. The present study reports the novel green synthesis of stable ZnO NPs using various concentrations of zinc nitrate (0.01M, 0.05M, 0.1M) and Albizia lebbeck stem bark extracts as an efficient chelating agent. Antimicrobial, antioxidant, cytotoxic, and antiprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(108 citation statements)
references
References 43 publications
16
83
0
Order By: Relevance
“…SEM imaging with EDX analysis was done to further confirm the presence of synthesized nanoparticles. From the SEM images of Figure 8 a and Figure 9 a, the zinc oxide nanoparticles synthesized from pomegranate leaf (ZnO-NPs-PL) shows an uneven round structure, which is similar to that reported by Umar et al [ 37 ] and Wali et al [ 54 ], and the presence of agglomerated nanoparticles can be seen on the SEM image. The SEM image of ZnO-NPs-PF ( Figure 9 a) also reveals an irregularly shaped microstructure with protrusions which seem flower-like.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…SEM imaging with EDX analysis was done to further confirm the presence of synthesized nanoparticles. From the SEM images of Figure 8 a and Figure 9 a, the zinc oxide nanoparticles synthesized from pomegranate leaf (ZnO-NPs-PL) shows an uneven round structure, which is similar to that reported by Umar et al [ 37 ] and Wali et al [ 54 ], and the presence of agglomerated nanoparticles can be seen on the SEM image. The SEM image of ZnO-NPs-PF ( Figure 9 a) also reveals an irregularly shaped microstructure with protrusions which seem flower-like.…”
Section: Resultssupporting
confidence: 84%
“…Bhuyan et al [ 36 ] also reported formation of a whitish precipitate. In contrast, Umar et al [ 37 ] observed a change in color from brown to a dark brown color on addition of Albizia lebbeck leaf extract to the precursor zinc acetate.…”
Section: Methodsmentioning
confidence: 93%
“…In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects. Inflammation and oxidative stress are closely related to arrhythmia [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Umar et al, cell membrane blebbing is an indication of cell apoptosis. 56 The high antiproliferation activity of OGEO-TMCNPs on MDA-MB-231 breast cancer cells compared to the remaining nanoparticles and OG extracts were likely due to the generation of oxidative stress with the cell membrane. 53 A summary of the entire process involved in the synthesis of OGEO-loaded nanoparticles and their in vitro biomedical applications is presented in Figure 15.…”
Section: Gratissimum Methanolic Extract Eos and Eo-loaded Nanopartimentioning
confidence: 98%